2016
DOI: 10.3906/bot-1508-4
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Turkish Pyronemataceae from Gaziantep Province

Abstract: Fourteen pyronemataceous macrofungi taxa (Aleuria exigua Rifai; Cheilymenia catenipila J. Moravec; Cheilymenia vitellina (Pers.) Dennis; Geopyxis majalis (Fr.) Sacc.; Geopyxis vulcanalis (Peck) Sacc.; Humaria aurantia (Clem.) Häffner, Benkert & Krisai; Kotlabaea deformis (P. Karst.) Svrček; Pulvinula johannis Lantieri; Pyronema domesticum (Sowerby) Sacc.; Scutellinia trechispora (Berk. & Broome) Lambotte; Smardaea planchonis (Dunal ex Boud.) Korf & W.Y. Zhuang; Tricharina ochroleuca (Bres.) Eckblad; Tricharina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…Consulting the current mycobiota checklists (Sesli & Denchev 2008 and the recent contributions regarding ascomycetes in Turkey (Güngör et al 2015, Kaya et al 2016, Şen et al 2016, we have concluded that Scutellinia legaliae is a new record for the mycota of Turkey. With the present study, the number of species reported in this genus rises to five.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Consulting the current mycobiota checklists (Sesli & Denchev 2008 and the recent contributions regarding ascomycetes in Turkey (Güngör et al 2015, Kaya et al 2016, Şen et al 2016, we have concluded that Scutellinia legaliae is a new record for the mycota of Turkey. With the present study, the number of species reported in this genus rises to five.…”
Section: Discussionmentioning
confidence: 73%
“…It now includes approximately 50 taxa throughout the world (Kirk et al 2008, Han et al 2010, Choi et al 2013. However only four Scutellinia species have been reported up to now from Turkey (Sesli & Denchev 2008, Kaya 2009, Akata et al 2011, Alli et al 2011, Kaya et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current checklists (Sesli and Denchev, 2014;Solak et al, 2015) compiled 34 pyronematous macrofungi existing in Turkey. After the latest versions of the checklists 28 members of Pyronemataceae have also been added to these lists and the total taxa number reached to 62 (Keleş et al, 2014;Türkoğlu and Castellano, 2014;Demirel et al, 2015;Karacan et al, 2015;Kaya and Uzun, 2015;Kaya et al, 2016;Kaya, 2016). As a result of this study, the number of pyromenatoid species known from Turkey has increased from 62 to 63.…”
Section: Discussionmentioning
confidence: 83%
“…The number of these investigations have been increased especially for the last decade and the collected data were presented as checklists by different research groups (Doğan et al, 2005;Sesli and Denchev, 2008). Recently, some new contributions were also added to list from different part of Turkey (Acar et al, 2015;Akata, 2017;Akata and Doğan, 2015;Akata and Uzun, 2017;Akata et al, , 2016a2016b;Akçay and Uzun, 2016;Alkan et al, 2016;Allı et al, 2016;Demirel and Koçak, 2016;Doğan and Akata, 2015;Doğan and Kurt, 2016;Dülger and Akata, 2016;Kaya et al, 2016;Topçu Sesli, 2016, 2017;Sesli and Vizzini, 2017;Öztürk C. et al, 2017;Öztürk Ö. et al, 2016;Taşkın et al, 2016;Vizzini et al, 2016;Uzun et al, 2017). The taxonomic investigations around the study area are conducted by Akata (2017); Allı et al (2016), Karamanoğlu and Öder (1973), Solak and Gücin (1992), but there is not any report of mycological investigation in Yalova province.…”
Section: Introductionmentioning
confidence: 99%